Immunohistochemical and molecular profile of salivary gland cancer in children. Issue 9 (31st January 2017) - Locati, Laura D.; Collini, Paola; Imbimbo, Martina; Barisella, Marta; Testi, Adele; Licitra, Lisa F.; Löning, Thomas; Tiemann, Katharina; Quattrone, Pasquale; Bimbatti, Emanuela; Chiaravalli, Stefano; Casanova, Michela; et al.
Abstract: Background: Pediatric salivary gland carcinomas (SGCs) are very rare. They differ from the adult SGCs in terms of epidemiologic and clinical behavior, being generally limited only to selected histotypes (e.g. low‐grade mucoepidermoid [LG‐MEC] and acinic cell cancer [AcCC]) and characterized by very good outcome. Our aim was to investigate therapeutic targets on a series of pediatric SGCs by immunohistochemical and molecular analysis. Methods: A retrospective analysis was performed to search for cases of pediatric SGCs in the database of the Pediatric Oncology Unit at the Istituto Nazionale Tumori and in the Pathology database at the Gerhard‐Seifert‐Reference‐Centre. The expressions of the most common tyrosine‐kinase receptors (TKRs) reported in adult SGCs as EGFR, HER2, KIT and hormonal receptors (HRs) (estrogen α and β, progesterone as well as androgen receptors) were investigated. CRTC1 / MAML2 and MYB/NFIB were also analyzed in MEC and adenoid cystic carcinoma cases, respectively. Results: Twenty‐nine cases were identified: 22 MECs, 4 AcCCs, 1 adenoid cystic carcinoma (ACC), 1 adenocarcinoma not otherwise specified and 1 sialoblastoma. EGFR was the most expressed TKR, whilst HRs were negative in all cases except for ER‐β in four cases of MEC. CRTC1 / MAML2 was present in 15 out of 17 evaluable MEC cases and MYB/NFIB was identified in the ACC case. Conclusions: The immunohistochemical and molecular profiles of pediatric SGCs analyzed in our series are similar to that observed in adults, especially for MEC, supporting a common biological background.